Implementasi Hak Anak dalam Perspektif Hukum Islam di Raudhatul Athfal - Fanreza, Robie; Harfiani, Rizka (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
The purpose of this study is to analyze the implementation of childrens rights in the perspective of Islamic law in Raudhatul Athfal. The research was conducted at Raudhatul Athfal (RA) Ar-Rashid located at Suka Maju Indah Estate, GG Block No. 1, Suka Maju, Sunggal, Deli Serdang, North Sumatera. This research uses qualitative approach with descriptive method. Technique of collecting data sourced from result of observation, interview and documentation. Research subjects were teachers, parents and children (students) in RA. Ar-Rashid. Data analysis using descriptive technique. The results of the research that are: (1) Rights of the Child in the perspective of Islamic Law, (2) Convention on the Rights of the Child (CRC) and (3) Implementation of childrens rights in early childhood Islamic education institutions Raudhatul Athfal, at a good implementing, manifest in the curriculum applied in Raudhatul Athfal. Starting from the right to get affection, domisile, education, health, all of which are included in the structure of early childhood education curriculum.